Second derivative multistep method for solving first-order ordinary differential equations - Turki, Mohammed Yousif; Ismail, Fudziah; Senu, Norazak; Ibrahim, Zarina Bibi (AIP Publishing, 2016)
In this paper, a new second derivative multistep method was constructed to solve first order ordinary differential equations (ODEs). In particular, we used the new method as a corrector method and 5-steps Adam’s Bashforth method as a predictor method to solve first order (ODEs). Numerical results were compared with the existing methods which clearly showed the efficiency of the new method.